Anteseden Penyerapan Tenaga Kerja Pada Sektor Usaha Pengolahan Ikan Desa Sumare Kabupaten Mamuju - Muhtar, Muhtar; Sudirman, Sudirman (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
Public concern for health provides an attraction for consuming food products that have a high protein intake, so that the consumption pattern of people on products made from fish is part of the four healthy and five perfect diet. There is a fish processing business in Sumare Village, Simboro Subdistrict, Simboro Subdistrict, Mamuju Regency, currently there are 32 fish processing businesses formed in Sumare Village spread across 10 hamlets in Sumare Village. This type of fish processing business is capable of absorbing a workforce of around 128 workers, where if on average one fish processing business can absorb a workforce of four workers. The lack of working capital used in production will certainly have a direct effect on business productivity, where currently fish processing businesses in Sumare Village still use simple equipment in the form of kitchen utensils, not one of the eight types of fish processing businesses uses technology equipment. , where when technology is available in the production of fish processing, this happens because of limited working capital so that it has a direct impact on the business productivity of fish processing businesses in Sumare Village, Simboro Village, Simboro District, Mamuju Regency.